Answer:
p > 2
Step-by-step explanation:
Answer:
Graph #1
Step-by-step explanation:
Compare your
y - 1 = (2/3)(x - 3) to
y - k = m(x - h). We see that k = 1 and h = 3.
Thus, (1, 3) is a point on the graph. This matches Graph #1.
Note: Graph #1 and Graph #3 appear to be the same. Why?
Answer:
first find the surface area of one of the square and one of the triangle.
then multiple it by the number of square and triangle they have
finally add the total surface area of the triangle with the total surface area of the square.
Step-by-step explanation:
- for one square
area= base * width
= 10*10
=100
total area of square= number of square * area of one square
t=6*100
t=600
area = 1/2 base * height
= 1/2 *10*8.66
=43.3
total area of triangle=number of triangle* area of one triangle
t2=8*43.3
=346.4
total surface area= total surface area of the square+ total surface area of the triangle
=600+346.4
=946.4 in^2
4/7 is the answer.
I cant reall explain becuase it will take forever xD
Minutes is the x axis and the yards the y axis
3,17